2016
DOI: 10.1186/s13027-016-0047-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis and phylogenetic analysis of human papillomavirus type-16 from suspected patients in Pakistan

Abstract: BackgroundHuman Papillomavirus (HPV) is well known pathogen that can cause benign and malignant tumors in humans, yet there is very little information regarding HPV types prevalent in Pakistan.MethodsA total of 92 cervical secretions were collected from suspected married female patients and used for DNA isolation using a novel isolation method. The samples were tested through Polymerase Chain Reaction (PCR) using already reported primers MY09/MY11, GP5/GP6, GP5+/GP6+, CP65/CP70, CP66/CP69 and SPF1/SPF2 and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 52 publications
(61 reference statements)
3
25
1
Order By: Relevance
“…Finally, the Xpert HPV assay was not always used as a point of care test, since there was a significant delay between sample collection and HPV analysis, which resulted in number of invalid results among s-DRY samples. This is consistent with a previous study performed in field conditions in Madagascar, where dry swabs stored at room temperature were used [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…Finally, the Xpert HPV assay was not always used as a point of care test, since there was a significant delay between sample collection and HPV analysis, which resulted in number of invalid results among s-DRY samples. This is consistent with a previous study performed in field conditions in Madagascar, where dry swabs stored at room temperature were used [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…In HIV infected women the risk of acquiring HPV is even higher due to immune suppression caused by HIV infection which has the same epidemiological pattern as HPV in sub-Saharan Africa [ 5 , 6 ]. In most of these cases infection with multiple genotypes has been found to predominate [ 5 , 7 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic adenocarcinoma is the fourth‐leading cause of cancer death in the United States 8, 18. Although surgery is the only established curative treatment option, 80% of patients with pancreatic cancer are not surgical candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that dose escalation can increase survival for pancreatic patients, further increasing the need to clearly visualize and accurately delineate the tumor for treatment planning 7, 17. Fortunately, recent efforts have been dedicated to using dual‐energy computed tomography (DECT) as an optimal CT modality to increase the detectability of pancreatic tumors 4, 6, 8, 9, 10, 12, 16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation